Inflammasome modulation with P2X7 inhibitor A438079-loaded dressings for diabetic wound healing - Yaron, Jordan R.; Bakkaloglu, Selin; Grigaitis, Nicole A.; Babur, Farhan H.; Macko, Sophia; Rhodes, Samantha; Norvor-Davis, Solenne; Rege, Kaushal (Frontiers in Immunology, 2024)
The inflammasome is a multiprotein complex critical for the innate immune response to injury. Inflammasome activation initiates healthy wound healing, but comorbidities with poor healing, including diabetes, exhibit pathologic, sustained activation with delayed resolution that prevents healing progression. In prior work, we reported the allosteric P2X7 antagonist A438079 inhibits extracellular ATP-evoked NLRP3 signaling by preventing ion flux, mitochondrial reactive oxygen species generation, NLRP3 assembly, mature IL-1 release, and pyroptosis. However, the short half-life in vivo limits clinical translation of this promising molecule. Here, we develop a controlled release scaffold to deliver A438079 as an inflammasome-modulating wound dressing for applications in poorly healing wounds. We fabricated and characterized a tunable thickness, long-lasting silk fibroin dressings and evaluated A438079 loading and release kinetics. We characterized A438079-loaded silk dressings in vitro by measuring IL-1 release and inflammasome assembly by perinuclear ASC speck formation. We further evaluated the performance of A438079-loaded silk dressings in a full-thickness model of wound healing in genetically diabetic mice and observed acceleration of wound closure by 10 days post-wounding with reduced levels of IL-1beta at the wound edge. This work provides a proof-of-principle for translating pharmacologic inhibition of ATP-induced inflammation in diabetic wounds and represents a novel approach to therapeutically targeting a dysregulated mechanism in diabetic wound impairment.